THE CHANGES OF AVAILABILITY INDEX OF PRODUCT OF CONTACTING PARTS OF VALVES IN EXPLOITATION PROCESS - Ситніков, А. Е.; Федоричко, Я. Б.; Маринець, Д. В. (Science-based technologies, 2009)
The outcomes of researches of change of availability index of product of contacting parts of valves with a solenoid drive are resulted, which one take place during their exploitation.